Airborne Release Fraction of Dissolved Materials During the Combustion of Liquids Representative of Nuclear Waste Treatment Process. (1st February 2023) - Ouf, F.-X.; Andrade, M. De Mendonca; Feuchter, H.; Duval, S.; Volkringer, C.; Loiseau, T.; Salm, F.; Ainé, P.; Cantrel, L.; Gil-Martin, A.; Hurel, F.; Lavalette, C.; et al.
Abstract: Experimental results are reported on the airborne release, under fire conditions, of hazardous materials dissolved in a mixture of organic solvents [tributylphosphate (TBP) and hydrogenated tetrapropylene (HTP)] representative of the nuclear fuel recycling process. Cerium and ruthenium have been considered, respectively, as stable and volatile fission products that eventually could be released as airborne particles during thermal degradation of contaminated and inflammable liquids. Airborne release fractions (ARFs) and their experimental uncertainties have been determined. Considering fire involving contaminated organic solvents, higher ARFs are reported for ruthenium Ru(+III) (0.99 ± 1.20%) in comparison with cerium [0.22 ± 0.31% and 0.20 ± 0.28% for Ce(+III) and Ce(+IV), respectively]. This discrepancy is partially due to the volatility of ruthenium formed under these conditions. Considering configurations involving an aqueous nitric acid phase placed below contaminated solvents, boiling of this phase enhances the release of contaminant materials: 1.78 ± 1.06% and 1.01 ± 1.31% for Ce(+III) and Ce(+IV), respectively, and 12.41 ± 29.45% for Ru(+III). Analysis of the size distribution, morphology, and chemical composition of the released particles and droplets emitted during HTP/TBP bubble collapse are reported, highlighting the contribution of bubble bursting at the solvent surface to airborne release.